An overview of Aloe vera impact on the healing process of Diabetic Foot Ulcer - Kania, Anna; Kałużyński, Grzegorz; Pełka, Maciej; Fijałkowska, Justyna; Ciulkiewicz, Łukasz (Journal of Education, Health and Sport, 2024)
Introduction and aim Diabetic foot ulcer (DFU) is a chronic condition that affects an increasing number of people each year[1]. Healing the ulceration requires cooperation between patients, specialists and scientists in order to achieve satisfactory results. Treating this type of wound is not only a therapeutic challenge[1,2,3,4,5,6], but also an economic one, which is why so much scientific research has already been made on this phenomenon[2,3]. Still scientists continue their quest for new cost-effective alternatives to current therapeutic options that would be consistent with contemporary knowledge and available engineering capabilities in pursuance of creating techniques and new dressings that will accelerate the healing of DFUs[2,3,7,8]. Factors such as stress, obesity, certain medications, and chronic diseases appear to negatively affect the process of repair [1,9,10,4,6,11]. Studies prove that aloe vera gel due to its healing properties, can be considered as a potential dressing that will expedite the mending process of diabetic foot ulceration[12,13,14]. In this paper, we performed a literature review of the applicability of aloe vera in the healing process of DFUs. Materials and methods Searching the available literature, including randomized clinical trials and systematic reviews, we drew on databases focusing on the effects of treatment for diabetic foot ulceration using Aloe vera. Conclusion: The current scientific research on the use of Aloe vera gel in diabetic foot ulcer treatment indicates that this method is safe, effective and inexpensive[2,3]. However the difficulty of treatment and the increasing prevalence of this type of wound pose a challenge to finding new solutions and exploring mechanisms in which aloe vera can have a possible role in the wound healing process. Nevertheless, this paper presents a promising impact of Aloe vera gel applicability in the healing process of diabetic foot ulcer.